Pelaporan Pajak Penghasilan Pasal 23 Atas Sewa Kendaraan Pada CV.XYZ - Widanti Eka Waluyi (FAKULTAS ILMU SOSIAL DAN ILMU POLITIK, 2026)
This Final Project Report aims to analyze the implementation of Income Tax (PPh) Article 23 reporting on vehicle rental transactions at CV. XYZ and to assess its compliance with applicable tax regulations in Indonesia. Article 23 PPh is a tax withheld on income received by domestic taxpayers and permanent establishments derived from capital, the provision of services, or certain gifts and awards, including income from vehicle rentals. Data was obtained through observation, interviews, and documentation related to vehicle rental transactions and the reporting of PPh Article 23 at CV. XYZ. The research results indicate that CV. XYZ has carried out the withholding and reporting of PPh Article 23 on vehicle rentals in accordance with applicable rates and regulations. Withholding of Income Tax Article 23 is performed by the payer, not the recipient. Thus, when the income recipient receives the income payment, the amount has already been reduced by tax, and they will receive a withholding certificate as an official record. The reporting process is conducted through the electronic tax administration system (Coretax) established by the Directorate General of Taxes.
Finalisasi Juli 2026 hasyim
Keywords: PPh 23; Pajak Penghasilan; Pelaporan Pajak; Sewa Kendaraan